Challenges and Opportunities of the Translate Method in Arabic Teaching in the Era of Digital Technology - Zulhaiki; Azis, Abdul (Pascasarjana Universitas Islam Negeri Mataram, 2024)
This research aims to explore the challenges and opportunities of the translate method in teaching Arabic in the era of digital technology. This study uses a literature study approach by analyzing literature that discusses the integration of technology in language education. The results of the study show that the translate method remains relevant if adjusted to technological developments with digital media, such as learning applications, visual aids, and audiovisual media. This media allows the learning process to be more interactive, contextual, and interesting for students. However, the study also reveals a major challenge that must be overcome, namely the need for training for students and teachers in evaluating automatic translation results. It is important to ensure that technology is used as a tool that complements a deep understanding of the text, not just replaces it. Teaching Arabic with the translate method in the digital era requires innovation to maintain its effectiveness and relevance in facing the needs of modern learning. The integration of technology in the teaching of the translate method must be done wisely to overcome the limitations of traditional methods while maximizing the opportunities offered by the digital era. This study provides practical recommendations to develop Arabic teaching approaches that are responsive to the needs of the times. With the right adaptation, the translate method can be an effective tool to improve students' ability to understand Arabic texts, as well as create a more meaningful, innovative, and relevant learning experience in the era of digital technology.